Three Dimensional Computational Fluid Dynamics Analysis of a Proton Exchange Membrane Fuel Cell - Sajad Alah Rezazadeh; Iraj Mirzaie; Nader Pourmahmoud; Nima Ahmadi (Journal of Renewable Energy and Environment, 2014)
A full three-dimensional, single phase computational fluid dynamics model of a proton exchange membrane fuel cell (PEMFC) with both the gas distribution flow channels and the Membrane Electrode Assembly (MEA) has been developed. A single set of conservation equations which are valid for the flow channels, gas-diffusion electrodes, catalyst layers, and the membrane region are developed and numerically solved using a finite volume based computational fluid dynamics technique. In this research some parameters such as oxygen consumption, water production, temperature distribution, ohmic losses, anode water activity, cathode over potential and the fuel cell performance for straight single cell were investigated in more details. The numerical simulations reveal that these important operating parameters are highly dependent to each other and the fuel cell efficiency is affected by the kind of species distribution. So for especial uses in desirable voltages, for preventing from the unwilling losses, these numerical results can be useful. Finally the numerical results of proposed CFD model have been compared with the published experimental data that represent good agreement.